Thermodynamic stability analysis of AlxCrMn5MoTi high-entropy alloys for high-temperature applications: A CALPHAD-assisted approach - Ben Festus; Phahlane Thabang A.; Ukpong Aniekan M.; Olubambi Peter A. (MATEC Web of Conferences)
In lightweight high-entropy alloy development, a titanium- aluminium (TiAl) base matrix is favored for its low density, high strength- to-weight ratio, and excellent corrosion resistance. Multi-component alloys using TiAl have shown stability under high temperatures. This study aimed to develop a high-entropy alloy by adding chromium (Cr), manganese (Mn), and molybdenum (Mo) to the TiAl base matrix, forming an AlxCrMn5MoTi alloy. CALPHAD models were employed to establish phase stability and phase formation rules were used to assess thermodynamic stability. The resulting AlxCrMn5MoTi alloy features a body-centered cubic solid-solution phase, a solidus temperature exceeding 1600°C, a density under 6.2 g/cm³, and a Young's modulus of over 190 GPa. The thermodynamic properties measured include mixing entropy (10.9 to 11.9 J/K), mixing enthalpy (-11.5 to -18.1 kJ/mol), an Omega parameter (Ω) of at least 1.1, an atomic size difference (δ) no greater than 6.6%, and a valence electron concentration (VEC) ranging from 4.89 to 4.83. The AlxCrMn5MoTi alloy shows significant promise for transportation, energy, and industrial applications, meeting the demands for lightweight, high-temperature, and corrosion- resistant materials.